Protecting electronic systems from power supply variations - Becker, Joe (Water engineering & management, 1995)
Coordinated power protection for water and wastewater facilities is considered in this article. Some recommendations are made regarding the proper installation and grounding of devices. These help ensure that every element of a plant facility is protected against lightning and power surge damage. A diagram of a typical layout of a properly staged transient voltage suppression in a water facility is also presented.